O Exame Nacional do Ensino Médio: uma política reconstruída por profesores de uma escola pública paulista - Piunti, Juliana Cristina Perlotti (2015)
The public high school education in Brazil is a victim of the constant reformism that has been hindering the strengthening of the own identity of this education period. The more frequent and abundant use of the High School Education National Exam as the gateway to undergraduate studies in the country has had repercussion to the educational institutions, students and teachers, who live the consequences of the popularization of this exam on their professional activities. The goal of this thesis is to understand the perspective of high school teachers of a specific school in Sao Paulo about the repercussions of the High School Education National Exam (ENEM - Exame Nacional do Ensino Médio) on their professional teaching practices. Our research developed with a qualitative approach, used bibliographical research on the high school and the High School Education National Exam, characterization instrument and interviews with five teachers and one teacher coordinator of a Sumare (city in the State of São Paulo) state school, in addition to the elaboration of the researcher's field journal. Our focus was on the reconstruction of the evaluation approach by the teachers, since we work on the theoretical assumption that every educational policy is reconstructed and remeant by the subjects that receive it. The basic concepts of the area of teacher formation that guided our study were: constants of the teaching work, teaching identity and teacher development. Aside from those, we also searched for knowledge about evaluation and some policies towards the high school education in Brazil. Based on the research, we could consider that the isolated work of a teacher, the opportunities of specific teaching activities, the non-reflected consumption of the political proposal are some of the conditions based on in which the teacher acquires their professional identity in this context. However, when searching for alternatives of teaching practices, when searching for answers to challenges in a collective manner, when feeling accomplished by their role as an experience creator to the students that find in the High School Education National Exam (ENEM - Exame Nacional do Ensino Médio) their source of hope to achieve the undergraduate studies, the teacher learns and develops themselves professionally, finding strategies to remain in the teaching activities. Our research indicates that the implementation of an educational policy that does not consider the formation process of the teachers, their objective work conditions and their perspective of this policy weakens their potential to induce changes on the curriculum, teaching practices and in the learning evaluation.